Các hợp chất đitecpenoit phân lập từ quả cây na biển (Annona glabra) (Phần 1) - Kiệm, Phan Văn; Thu Hiền, Nguyễn Thị; Yến, Phạm Hải; Dung, Dương Thị; Thúy Hằng, Đan Thị; Nhiệm, Nguyễn Xuân; Đức, Trần Minh; Bản, Ninh Khắc; Tuấn Anh, Hoàng Lê; Minh, Châu Văn (Vietnam Journal of Chemistry, 2015)
Four kaurane diterpenoids, 16β,17-dihydroxy-ent-kaurane (1), 16β,17-dihydroxy-ent-kauran-19-al (2), 16β,17-dihydroxy-ent-kauran-19-oic acid (3) and 16α,17-dihydroxy-ent-kaurane (4) were isolated from the methanol extract of the Annona glabra fruits by various chromatographic experiments. Their structures were characterized and revised by 1D-, 2D-NMR spectra, and ESI-MS, as well as in comparison with the reported values.